IDENTIFYING FEBRILE HUMANS USING INFRARED THERMOGRAPHY SCREENING: POSSIBLE APPLICATIONS DURING COVID-19 OUTBREAK - Silvino, Valmir Oliveira; Gomes, Regis Bernardo Brandim; Ribeiro, Sérgio Luiz Galan; Moreira, Davyson de Lima; Santos, Marcos Antonio Pereira dos (Revista Contexto & Saúde, 2020)
Since the first case of COVID-19 reported at late 2019, it has quickly spread throughout the world and became a pandemic. Because of its high transmission rate, COVID-19 is a huge threat to public health worldwide. Fever is a common symptom of patients with severe acute respiratory syndromes (SARS), including the COVID-19 disease. Infrared thermography (IT) is widely used to mass-screen the skin temperature of people in crowded places, such as hospitals and airports. This is of importance for patients and health professionals as it drastically decreases the risk of transmission due to the minimal contact between the evaluator and the subject. Infrared thermography strategy has already been widely used for the screening of febrile people during the outbreak of other pandemics such as H1N1 and Ebola. We here describe the potential of IT to identify febrile people who may be infected with COVID-19 and provide recommendations for their monitoring and management during this pandemic based on literature data.